STRATEGI KOMUNIKASI PEMASARAN TSHIRTTOKOH DALAM MEMBANGUN KESADARAN MEREK - Kurniawati, Sherliana; Sekar Wangi, Maya; Muadz, Muadz (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
Tshirttokoh is a clothing line brand from Solo that utilizes social and political issues to create designs for its products. The aim of this research was to find out how the marketing communication strategy for Tshirttokoh in building brand awareness. This research uses a qualitative descriptive research method with data collection techniques of observation, documentation and interviews. In collecting data, researchers conducted interviews with company owners, employees as designers, interviews with Tshirttokoh consumers, and conducted surveys via questionnaires with the aim of measuring the level of brand awareness. Based on the results of the research analysis, the owner of Tshirtokoh carries out a marketing communication strategy in building brand awareness, namely through sales promotion activities, direct marketing, events and experiences, word of mouth marketing. The conclusion of this research is that it is analyzed using the IMC (Integrated Marketing Communication) concept. In the marketing communication strategy of Tshirttokoh, a marketing tool was found that was able to build brand awareness at the brand recognition level, namely word of mouth marketing. In the future, it is hoped that Tshirttokoh can reach the peak level of top of mind brand awareness. Keywords: Marketing Communication Strategy, Brand Awareness, Tshirttokoh